In Situ Surface Polymerization of PANI/SWCNT Bilayer Film: Effective Composite for Improving Seebeck Coefficient and Power Factor - Dezhuang Ji; Baosong Li; Balamurugan Thirumal Raj; Xuan Li; Dawei Zhang; Moh'd Rezeq; Wesley Cantwell; Lianxi Zheng (Advanced Materials Interfaces)
Abstract Flexible thermoelectric composites are promising in harvesting low‐temperature energies and have a wide range of applications in wearable devices. However, the uncontrollable interfaces between the components significantly scatter the transport of electrons leading to a reduced thermoelectric performance. In this research, hydrochloride acid doped polyaniline (PANI) is directly prepared on the surface of a single‐walled carbon nanotube (SWCNT) film to form a bilayer structure in controlling the interfacial filtering effect and preserve the high conductivity. Under optimal conditions, a PANI/SWCNT bilayer composite exhibits a Seebeck coefficient of 26 µVK−1 at near room temperature, and a high electrical conductivity of 1320 S cm−1 is maintained. The Seebeck coefficient is a twofold increase compared to a pure SWCNT film, while the power factor is three times the value from a pure SWCNT film and 500 times that from a solution‐mixed PANI/SWCNT composite. The enhanced thermoelectric performance is attributed to SWCNT‐assisted growth through π–π interaction promoting the formation of an oriented and compacted PANI layer, and the bilayer structure can also maximally maintain the electrical conductivity of the composite. The bilayer composite has then been investigated as an energy harvester and a temperature sensor, indicating its reliable performance in wearable applications.